Pancasila Student Profile Strengthening Project As Implementation of The Independent Curriculum at Putra Putri Bangsa Primary School Lubuklinggau - Yulianti, Yulianti; Danim, Sudarwan; Badeni, Badeni; Kristiawan, Muhammad; April Yanti, Fitri (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to find out how the project to strengthen the profile of Pancasila students is implemented as an implementation of the independent curriculum at the Lubuklinggau Nation Primary School for Boys and Girls. The method used in this research is qualitative. The research subjects consisted of 1 school principal, 2 teachers and 2 students. The research location is Putra Putri Bangsa Elementary School, Lubuklinggau City. The research results show that Putra Putri Bangsa Elementary School has implemented an independent curriculum since 2022, currently, Putra Putri Bangsa Elementary School is in the Freedom to Change category. The classes that have implemented the independent curriculum are Class I and Class IV. The Independent Curriculum gives educators the freedom to create quality learning that suits students' needs and learning environment. The characteristics of an independent curriculum include Soft Skills and Character Development, Focus on Essential Material, and flexible learning. In implementing the independent curriculum, schools must carry out projects to strengthen the profile of Pancasila students. The project is not directed at achieving specific learning achievement targets, so it is not tied to subject content. Putra Putri Bangsa Elementary School has implemented project-based learning and inquiry learning before the implementation of the independent curriculum, where these two methods are methods that must be used in the independent curriculum. So that Putra Putri Bangsa Elementary School does not have difficulties and obstacles in implementing the independent curriculum. The project to strengthen the profile of Pancasila students has been carried out in the form of student performance. Student performance is an annual routine agenda that has long been carried out by SD Putra Putri Bangsa. Student performance activities are carried out in even semesters. In 2023, the theme of student performance activities is traditional art. This project has proven successful in the planning, implementation, and assessment stages showing the six dimensions of the Pancasila profile